Development challenges of HIV/AIDS in small states : experiences from the Pacific, Southern Africa and the Caribbean - Theodore, Karl (Commonwealth Secretariat LondonGB, 2011)
Focuses on HIV/AIDS and about the experience of the epidemic in small states.Aims to provide a reasonably detailed picture of the impact of the epidemic and the response to it in circumstances where the countries, because of their small size, cannot afford to play host to this crippling epidemic.